AMTSAL KAMINAH DAN MURSALAH: PERBANDINGAN DAN KONTEKSTUALISASINYA - Haris, Abd; Tahir, Muhyiddin; Nurfaika, Nurfaika (TAFASIR: Journal of Quranic Studies, 2025)
This paper will trace the context of the parable in the Qur'an (amtsal al-Qur'an) by highlighting the criteria clearly of the amtsal described in the Qur'an. In addition, comparing the qur'anic amtsal between the kaminah amtsal and the mursalah amtsal which is not explicitly explained regarding its criteria as  the qur'an amtsal but by scholars has a contestation that amtsal mursalah falls into the category of amtsal. Some scholars say it does not fall into the realm of amtsal.  However, other scholars are not an obstacle when one wants to make the Qur'an an amtsal. Because the Quran essentially wants to be read, studied, recited until its mentadabburi. This paper uses library research with Mahmud Syahata's theory that the Qur'an shows its miracles through language style (asalib) which explains with a variety of meanings and wisdom for humans, both sensory and non-sensable, visible or not, contemporary problems to ukhrawi problems as a way to get mau'idzah hasanah.  The author's provisional finding that the variety  of amtsals of the Qur'an is essentially something that opens the horizons of human thought not to leave the Qur'an and continue to study it as a way to see the current context that cannot be separated from the image that Allah narrates in the Qur'an.